Pemodelan Numerik 1-D untuk Analisis Banjir Sungai Tungkal pada DAS Tungkal - Rian Mantasa Salve Prastica; Estu Wijayanti (Jurnal Proyek Teknik Sipil, 2021)
Kuala Tungkal has a stormwater runoff, namely the Pengabuan River which is the primary river flow. Pengabuan River is located in the Tungkal Watershed, Jambi Province. Flood problems occur due to high tide flow (tidal flood) and high rainfall. So, flood prevention planning needs to be done. Drainage planning efforts are expected to reduce the flood discharge from the overflow of the Pengabuan River. The purpose of this research is to identify the occurrence of floods in the Pengabuan River with Q100. This research uses secondary data, from daily rainfall for 10 years (2010-2019) from 3 rain stations (Japura, Muaro Jambi, and Meteorologi Dabo), Tungkal watershed map, as well as transverse and longitudinal images Pengabuan River. Step of calculation starts from the selection of daily rainfall data, the average rainfall with Polygon Thiessen method, frequency analysis, Chi-Square test, Smirnov Kolmogorov test, and planned flood discharge analysis by the HSS Nakayasu method. The discharge plan is used to analyze flood with the HEC-RAS program. The results showed that the planned flood discharge during 100 years was 12432.19 m3/s. the results of analysis of the existing HEC-RAS on the river cross section is overflow or flooding, it is necessary to re-dimension it.